Comparison of Brazilian Plants Used to Treat Gastritis on the Oxidative Burst of Helicobacter pylori-Stimulated Neutrophil. (18th July 2013) - Bonacorsi, Cibele; da Fonseca, Luiz Marcos; Raddi, Maria Stella Gonçalves; Kitagawa, Rodrigo Rezende; Vilegas, Wagner
Abstract : Ten Brazilian medicinal plants used to treat gastritis and ulcers were carefully selected on the basis of ethnopharmacological importance and antiulcerogenic activity previously described. The antioxidant activity of the methanolic extracts was determined in analysis conditions that simulate a real biological activity on inhibition of the oxidative burst induced in neutrophils using Helicobacter pylori as activator, by a luminol-amplified chemiluminescence assay. The extracts, at low concentration (5 μ g/mL), exhibited a large variation in inhibitory effects of H. pylori -induced oxidative burst ranging from 48% inhibition to inactive, but all extracts, excluding Byrsonima intermedia, had inhibitory activity over 80% at the concentration of 100 μ g/mL. The total suppressive antioxidant capacity measured as the effective concentration, which represents the extract concentration producing 50% inhibition of the chemiluminescence induced by H. pylori, varies from 27.2 to 56.8 μ g/mL and was in the following order: Qualea parviflora > Qualea multiflora > Alchornea triplinervia > Qualea grandiflora > Anacardium humile > Davilla elliptica > Mouriri pusa > Byrsonima basiloba > Alchornea glandulosa > Byrsonima intermedia . The main groups of compounds in tested extracts are presented. Differences in the phytochemical profile, quantitatively and qualitatively, of these plants can explain and justify their protective effect on the gastric mucosa caused by the neutrophil-generated ROS that occurs when H. pylori displays its evasion mechanisms.